A Comparison of Standard One-Step DDA Circular Interpolators with a New Cheap Two-Step Algorithm - Leonid Moroz; Jan L. Cieśliński; Marta Stakhiv; Volodymyr Maksymovych (Modelling and Simulation in Engineering)
We present and study existing digital differential analyzer (DDA) algorithms for circle generation, including an improved two-step DDA algorithm which can be implemented solely in terms of elementary shifts, addition, and subtraction.